Последнее пополнение Перещепинского сокровища его владельцем - Львова, З.А.; Маршак, Б.И. (Материалы по археологии, истории и этнографии Таврии, 1998)
A group of things from Peretschepino treasure, presumably made in the. residence of its owner not long before his death, is published in this article.